SYSTEMATIZATION OF THE APPROACHES ASSESSING SOCIO-ECONOMIC DEVELOPMENT OF THE COUNTRIES BY USING WELFARE INDEX - Balashova, S.A.; Nakhatakyan, E.O. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Ėkonomika, 2017)
Nowadays there is a lack of a unified approach to the welfare definition and methods for its assessment, therefore this article combines different welfare indices, analyzes their features, as well as the indicators that they include.The classification of these indices in accordance with the three theoretical approaches is suggested: objective, which is based on the statistical data; subjective, which is based on the subjective opinion of the population and objective-subjective, which combines both of the above mentioned approaches. The relevance of well-being indices is analyzed; it is also proven the interrelation of well-being indices with the traditional socio-economic indicators. It is defined that the correct assessment of well-being achieved by using objective-subjective indices, which take into account the statistical data as well as subjective opinion of the population.